2016
DOI: 10.1177/0091026016676093
|View full text |Cite
|
Sign up to set email alerts
|

Is Public Service Motivation a Better Explanation of Nonprofit Career Preferences Than Government Career Preferences?

Abstract: Public service motivation (PSM) is a multifaceted theory that explains, among other things, the career preferences of individuals. Some have suggested that PSM is not inherently government specific and thus is also a meaningful characteristic of individuals who are employed in the nonprofit sector. This study sought to add to this body of research by exploring the relationship that PSM has to nonprofit and government career preferences, while controlling for the influences of age, gender, minority status, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 84 publications
(127 reference statements)
4
31
0
Order By: Relevance
“…Importantly, the effects documented here observe a measure of intrinsic values prior to entering the workforce, controlling for bias introduced by workforce environment on measures of worker values and providing evidence of the direction of the relationship between PSM‐related values and sector selection. The positive relationship between PSM‐related values and selection into both public and nonprofit occupations is consistent with other recent evidence examining nonprofit workers (Bright ). The relationship between values and job choice seems related to educational attainment only to the extent that sorting occurs into majors within colleges before the labor market.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, the effects documented here observe a measure of intrinsic values prior to entering the workforce, controlling for bias introduced by workforce environment on measures of worker values and providing evidence of the direction of the relationship between PSM‐related values and sector selection. The positive relationship between PSM‐related values and selection into both public and nonprofit occupations is consistent with other recent evidence examining nonprofit workers (Bright ). The relationship between values and job choice seems related to educational attainment only to the extent that sorting occurs into majors within colleges before the labor market.…”
Section: Discussionsupporting
confidence: 90%
“…As Bright () notes, some high‐PSM workers with government experience report being less likely to seek a return to government careers after leaving. In conjunction with Bright's findings, the results presented here underscore that public and nonprofit management practices should consider the distinct motivation public sector workers carry with them into the workforce to avoid losing promising employees.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the US (Clerkin and Coggburn 2012;Rose 2012;Bright 2016) indicate that PSM is a better predictor of nonprofit career preferences. This study, in a European context, has found that student interest in the nonprofit sector is enhanced by self-sacrifice and compassion but reduced by commitment to public values.…”
Section: Discussionmentioning
confidence: 94%
“…Rose () found that young students were more likely to view the nonprofit sector rather than government as the place to work if they wanted to serve other people and society. Bright () also found that PSM is a significantly better predictor of nonprofit career preferences.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Cognitively, the information obtained will definitely influence students' sell efficacy in making career decisions [17]. The results of the study indicate that there is a tendency for someone to use social media services to choose careers that is prone to be unattached to strict rules such as working for the government [18].…”
Section: % 14% 13%mentioning
confidence: 94%